PENGARUH GREEN MARKETING DAN GREEN PRODUCT TERHADAP KEPUTUSAN PEMBELIAN PRODUK ECOBAG(Studi Kasus: Mall Kota Jambi) - Riski Melyana (ICONS: Islamic Economics Journal, 2026)
The purpose of this study is to determine: (1) To determine the significant influence of green marketing on the decision to purchase ecobag products in Jambi City Mall. (2) To determine the significant influence of green products on the decision to purchase ecobag products in Jambi City Mall. (3) To determine the significant influence of green marketing and green products on the decision to purchase ecobag products in Jambi City Mall. The research method used is a quantitative method with the analysis tool used is Multiple Linear Regression Analysis. The results of the study show that: (1) Green Marketing has an influence on the Decision to Purchase Ecobag Products with a significance value of 0.000 <0.05. If Green Marketing increases, the Decision to Purchase ecobag products in Jambi City Mall will also increase. (2) Green Products have an influence on the Decision to Purchase Ecobag Products with a significance value of 0.000 <0.05. If Green Products increase, the Decision to Purchase ecobag products in Jambi City Mall will also increase. (3) Green Marketing and Green Products have a joint influence on the Decision to Purchase Ecobag Products. The coefficient of determination indicates that green marketing and green products can influence purchasing decisions for ecobags at Jambi City Malls by 85.1%.